Valuing deliberate built-in flexibility in houses – exampled - Carmichael, David G.; Taheriattar, Reza (International Journal of Strategic Property Management, 2018)
People’s Housing requirements commonly transition over time, and there are financial, social and environmental impacts associated with altering and moving houses. With possible future alteration in mind, this paper looks at the viability of deliberately incorporating flexibility into houses at the time they are designed and built, as compared with no specifically incorporated flexibility (yet still possibly capable of being altered). A comparative analysis, rather than an absolute analysis, is outlined. The financial viability is performed as an options analysis, while the social and environmental matters are evaluated along life cycle assessment lines. As a case example, the paper considers the viability of incorporating deliberate two-storey flexibility into a single-storey house using Australian practices. It is shown on the case example that incorporating deliberate built-in flexibility can perform positively against all sustainability criteria – financial, social and environmental, separately or combined – however the generality of this conclusion remains to be proven.